Differentiable RANSAC (DSAC) for visual re-localization [data] - Brachmann, Eric (Universität, 2020)
Pre-trained models of our camera re-localization method for the MSR 7Scenes dataset. For more information, also see the code documentation: https:/...
Production date: 2016-10-31
Gesehen am 14.09.2020
Keywords: Forschungsdaten; Datenbank